Aqueous and nonaqueous microemulsion systems with a palm oil-base emollient - Suhaimi, Hamdan; R., Lizana; C.R., Laili (Springer-Verlag, 1995)
Microemulsions with a palm oil-based emollient, i.e., medium-chain triglyceride (MCT), and water or glycerol, stabilized by two oppositely charged ionic surfactants and a medium-chain alcohol, were investigated. The results showed that only the water-in-MCT or the glycerol-in-MCT microemulsions were prominent. The maximum solubilization of the MCT emollient was higher in cetyltrimethyl ammonium bromide, i.e., the positively charged surfactant that contained a nitrogen atom, than the negatively charged surfactant sodium dodecyl sulfate. However, the results did not lend themselves for selecting any decisive factor that would explain the different solubilization behavior encountered in the investigated aqueous and nonaqueous systems. © 1995 American Oil Chemists' Society.